Does Disclosure of Performance Information Influence Street‐level Bureaucrats' Enforcement Style?. (2nd March 2018) - de Boer, Noortje; Eshuis, Jasper; Klijn, Erik‐Hans
Abstract: Governments use different regulatory instruments to ensure that businesses owners or "inspectees" comply with rules and regulations. One tool that is increasingly applied is disclosing inspectees' performance information to other stakeholders. Disclosing performance information has consequences for street‐level bureaucrats because it increases the visibility of their day‐to‐day work. Using a survey (n = 507) among Dutch inspectors of the Netherlands Food and Consumer Product Safety Authority, this article shows that the disclosure of performance information has an impact on enforcement style at the street level. Findings show that perceived disclosed performance information positively enhances all three dimensions of street‐level bureaucrats' enforcement style (legal, facilitation, and accommodation). This effect is strongest for facilitation and accommodation and weakest for the legal style. Perceived resistance by inspectees partly explains this effect. Contrary to expectations, more perceived disclosure does not result in more but in less perceived resistance of inspectees by street‐level bureaucrats.